The Joplin Tornado, 2011 - Tarshis, Lauren; Dawson, Scott (New York : Scholastic Press, 2015)
A young boy is in the middle of one of the deadliest tornadoes to strike the United States since 1947.
Includes bibliographical references.
Keywords: Tornadoes -- Juvenile fiction -- Missouri; Survival -- Juvenile fiction; Tornadoes -- Fiction; Survival -- Fiction